Tracing Byron's influence on Nikolay Nekrasov - Kučerskaja, Majja Aleksandrovna (Primerjalna književnost, 2018)
The article investigates various facets of George Gordon Byron's influence on Nikolay Nekrasov. Traditionally, scholars have viewed these two poets as antipodes, belonging to different literary movements, Nekrasov to Realism and Byron to Romanticism. However, an analysis demonstrates that the themes and problematics of Byron's poetry, as well as the classic Byronic hero and motifs, remained relevant to Nekrasov throughout his entire literary career, beginning with his early collection Mechty i zvuki (1840), up to his poem Komu na Rusi zhit' khorosho (1877). Particularly the latter's structure was influenced by the structure of Byron's long poems.
Keywords: angleška poezija; Byron, George Gordon; literarni vplivi; Nekrasov, Nikolaj Alekseevič; romantika; ruska poezija